Evaluating the Efficacy of Tramadol as an Adjuvant to Intrathecal Isobaric Levobupivacaine for Elective Infraumbilical Surgeries - Singh, Dewan Roshan (Anesth Essays Res, 2017)
BACKGROUND: Long-acting local anesthetics are used in subarachnoid block to increase the duration of anesthesia. Adjuvants are added to improve the duration of analgesia. SETTINGS: Randomized controlled trial was conducted in the Department of Anesthesiology in a tertiary care hospital. AIMS AND OBJECTIVES: The objective of this study was to evaluate the efficacy of low-dose tramadol as an intrathecal adjuvant to levobupivacaine in terms of duration of analgesia, onset of sensory blockade, onset of motor blockade, and duration of motor blockade. METHODOLOGY: After obtaining the Institutional Ethics Committee approval and informed consent, sixty patients posted for infraumbilical surgeries were recruited. Randomization was done using a sealed envelope technique. Patients were divided into two groups: LT received 3 ml of 0.5% isobaric levobupivacaine with tramadol 10 mg (0.2 ml) and LS received 3 ml of 0.5% isobaric levobupivacaine with 0.2 ml of normal saline. Duration of analgesia, onset of sensory blockade, and onset and duration of motor blockade were recorded. RESULTS: There was no statistical difference in demographic data between the two groups. The mean onset time of sensory blockade in Group LS was 12.7 ± 9.81 min and for Group LT was 12.9 ± 0.81 min, which was not statistically significant between two groups (P = 0.93). The mean onset time of motor blockade in Group LS was 13.4 ± 10 min and for Group LT was 14.4 ± 10 min, which was no statistically significant between the two groups (P = 0.71). The mean time duration of analgesia in Group LS was 170.3 ± 59 min and for LT was 198.9 ± 57.33 min. There was mild prolongation of analgesia in Group LT, but it was not statistically significant (P = 0.0615). The mean duration of motor blockade in Group LS was 170.23 ± 58 min and Group LT was 190.76 ± 4 min, which was not statistically significant between the two groups (P = 0.14). CONCLUSION: Low-dose tramadol as an adjuvant to isobaric intrathecal levobupivacaine does not prolong analgesia significantly.